Теоретико-игровые подходы к исследованию экономических ситуаций - Kulikova, Valentina (2016)
The objective of that Bachelor`s Thesis is learning of certain methods of Game Theory which are useful as daily problems of people as process's in business conditions. The object of that Bachelor`s Thesis is a problem with production of public goods and the subject of the paperwork is a theoretical foundation of sections of Game Theory - statistic games of complete or incomplete information dynamic games of complete or incomplete information. The Bachelor`s Thesis was divided into three parts: Theoretical part, Practical part 1 (setting problems) and Practical part 2 (modeling the problems).